PENGUATAN PROFIL PELAJAR PANCASILA DALAM PENDIDIKAN KEWARGANEGARAAN MELALUI MEDIA PEMBELAJARAN INTERAKTIF - Shofia Nurun Alanur; Jamaludin; Sunarto Amus; Hasdin; Nasran (LPPM Universitas Muhammadiyah Bulukumba, 2024)
The digitalization of education, especially in Pancasila and citizenship education, is a challenge to maintain the existence of Pancasila values ​​in life. Advances in digital technology can be utilized to contribute to the transfer of knowledge, strengthening national character and the profile of Pancasila students, as long as it is used wisely. One of them is through the use of interactive learning media. This study aims to describe how to strengthen the profile of Pancasila students in citizenship education through learning media using the Mentimeter application. This study is a descriptive qualitative study with a data collection method using a questionnaire via Google Form. The informants of this study were 69 Pancasila and citizenship education students. The results of the study showed that there were four values ​​of the Pancasila student profile that emerged during learning, namely moral values ​​towards humans, critical reasoning values, global diversity values ​​and mutual cooperation values. Moral values ​​towards humans are reflected in the attitude of students who respect and respect the opinions of others and accept their group. Global diversity values ​​are reflected in the attitude of students who do not discriminate between religion, ethnicity and region of origin in working together. Digitalization can encourage the development of national character.